2000
DOI: 10.1002/(sici)1097-4636(200008)51:2<216::aid-jbm10>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-responsive culture dishes allow nonenzymatic harvest of differentiated Madin-Darby canine kidney (MDCK) cell sheets

Abstract: We have developed a temperature-responsive culture dish grafted with a poly(N-isopropylacrylamide) (PIPAAm). Various types of cells adhere, spread, and proliferate on the grafted dishes in the presence of serum at 37 degrees C. By reducing only temperature, these cells can be harvested noninvasively from the dishes according to rapid hydration of the grafted polymer. Because the harvest does not need enzymatic digestion, differentiated cell phenotypes are retained. In the present study, a renal epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 23 publications
3
93
0
Order By: Relevance
“…We speculate that inhibitory biological effects are involved in a high concentration of GO. Cells attach to hydrophobic surfaces via their cell membrane 47,48) , but 1 wt% GO films provide a fairly hydrophilic surface. Lee et al have demonstrated that contact angle of GO film was lower than that of reduced GO film without functional groups 14) .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that inhibitory biological effects are involved in a high concentration of GO. Cells attach to hydrophobic surfaces via their cell membrane 47,48) , but 1 wt% GO films provide a fairly hydrophilic surface. Lee et al have demonstrated that contact angle of GO film was lower than that of reduced GO film without functional groups 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Commercial devices that rely on the sharpness, tunability, reversibility, and reliability of this transition are now available in areas as varied as chromatography [1,2], microfluidics [3], cell culture, and tissue engineering [4,5]. These achievements have spurred a renewed interest in fundamental studies of polymer self-assembly at the air/water (A/W) interface particularly in the case of amphiphilic diblock copolymers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…33 Canavan et al investigated the location of laminin, fibronectin, and type I and type IV collagens after cell detachment from plasma polymerized PIPAAm. [5][6][7] Immunoassays revealed that most fibronectin and laminin detached together with the cell sheets after reducing temperature.…”
Section: Mechanism Of Cell Detachment From Temperature-responsive Surmentioning
confidence: 99%